Thermal, Spectral and Magnetic Studies of Complexes of Sebacic Acid Bis-hydrazide and Sebacic Acid Bis-2,4-Dinitrophenyl Hydrazide with Transition Metal Ions - Jahagirdar, H.G.; Juneja, H.D.; Munshi, K.N. (Asian Journal of Chemistry, 2010)
Present paper describes the work on the synthesis of sebacic acid bis-hydrazide [SABH] and sebacic acid bis-2,4-dinitrophenyl hydrazide and their complexes with Mn(II), Co(II), Ni(II), Cu(II) and Zn(II). The characterisation of these newly synthesised complexes have been done on the basis of elemental analysis and structural aspects have been studied using spectral, magnetic and thermochemical techniques. All these complexes have been found to have 1 : 1 composition and are insoluble in almost all the organic solvents. The position of chelate loop has been suggested on the basis of infrared spectral studies. Electronic spectral and magnetic studies provided information on the geometry of the complexes formed while thermal studies indicate comparatively high thermal stability associated with these complexes.